Evaluation of children and teenagers’ physical activity - Batyk, Iwona (Journal of Education, Health and Sport, 2011)
In days of progressive consumption of everyday life apart from professional duties, social, home and scientific, young people need to undertake active forms of intellectual or physical activity. Forms connected with motion activity can contribute to development of interests and personality. Also it can rise sport activity, unload the nervous tension and prevent the civilization diseases. The recreation is the voluntary activity and its forms are the result of type of interests and place of the people living. The activities are undertaken in spare time for rest to improve health and to entertain. They include all forms of activity not only motion and social improvement. The article presents the results of studies which concern the forms and the ways of spending spare time dedicated to motion recreation, main barriers connected with the motion recreation and costs connected with it. The article represents the children and teenagers' current profile of participation in motion recreation in the theory - verifying way. The studies had on aim opinion of pupils' motion shape from three kinds of schools: elementary school, gymnasium and high school and tested what form of activity are expected by children and teenager's.